Toward gene therapy for growth hormone deficiency via salivary gland expression of growth hormone. (13th January 2014) - Racz, GZ; Zheng, C; Goldsmith, CM; Baum, BJ; Cawley, NX
<x xml:space="preserve">Abstract</x> Objectives Salivary glands are useful targets for gene therapeutics. After gene transfer into salivary glands, regulated secretory pathway proteins, such as human growth hormone, are secreted into saliva, whereas constitutive secretory pathway proteins, such as erythropoietin, are secreted into the bloodstream. Secretion of human growth hormone (hGH) into the saliva is not therapeutically useful. In this study, we attempted to redirect the secretion of transgenic hGH from the saliva to the serum by site‐directed mutagenesis. Materials and Methods We tested hGH mutants first in vitro with AtT20 cells, a model endocrine cell line that exhibits polarized secretion of regulated secretory pathway proteins. Selected mutants were further studied in vivo using adenoviral‐mediated gene transfer to rat submandibular glands. Results We identified two mutants with differences in secretion behavior compared to wild‐type hGH. One mutant, ΔN1–6, was detected in the serum of transduced rats, demonstrating that expression of this mutant in the salivary gland resulted in its secretion through the constitutive secretory pathway. Conclusion This study demonstrates that mutagenesis of therapeutic proteins normally destined for the regulated secretory pathway may result in their secretion via the constitutive secretory pathway into the circulation for potential therapeutic benefit.